Bibliometric Analysis of Postgraduate Theses on Civil Aviation - KANBUR, Engin (Journal of Aviation, 2023)
This study aimed to conduct a bibliometric evaluation of 908 postgraduate theses in civil aviation that were approved, licensed, and published in the National Thesis Centre database. These theses were analysed based on specific parameters, including the year of publication, gender of the authors, universities where they were published, thesis topics, language of writing, number of pages, publication cities, supervisor titles, institutes, departmental affiliations, types of universities, and types of theses. The results revealed that most of these theses were published in 2019, and male researchers outnumbered female researchers. Moreover, many of the theses were written in Turkish and predominantly published at Anadolu University. The title of "assistant professor" was more commonly used in master's theses, while the title of "professor" was more frequently utilized in doctoral theses. Most of the theses were 101-200 pages long and were conducted in Istanbul. Based on the findings, it can be concluded that there were more master's theses than doctoral theses, with a predominant research focus on business management.
Keywords: İşletme; Civil Aviation; Bibliometric Analysis; Bibliometric; Business Administration; 4. Education